Penerapan Data Mining Pada Penjualan Kartu Paket Internet Yang Banyak Diminati Konsumen Dengan Metode K-Means - Turnip, Hendra Nicodemus; Fahmi, Hasanul (Jurnal Ilmu Komputer dan Sistem Informasi (JIKOMSI), 2021)
Currently, Royal Ponsel has a problem where to determine which internet package card consumers are most interested in from selling internet cards Telkomsel, XL, Axis, Im3, 3 (Tri), and Smartfren. A lot of information is owned but it is not enough if the information is not utilized properly, so it is necessary to group sales data to determine the competitiveness of which internet card products have the highest sales level based on sales in the Royal Ponsel business. Of course, this problem requires a technology that can analyze data on internet package card sales transactions. One of them is by applying data mining to the sale of internet package cards which are in great demand by using the K-Means Clustering method calculation. With the existence of grouping types of internet cards that are used to improve the performance of sales so as to determine the steps to increase stock on internet package cards appropriately.